2022
DOI: 10.20473/ijosh.v11isi.2022.19-30
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between Workers’ Characteristics and Workplace Noise with Subjective Hearing Disorders in Textile Industry

Abstract: Introduction: The textile manufacturing industry has a noisy work environment as a result of the weaving machines which have a noise intensity exceeding the threshold value. Noise can cause complaints of hearing disorders. Other factors that influence hearing disorders are agework period, and the use of ear protection equipment. This study aims to analyze the relationship between age, work period, the use of ear protection equipment, and noise intensity on complaints of subjective hearing disorders in the AJL … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 19 publications
1
1
0
Order By: Relevance
“…The current study recorded high significant relation between audiometric notches and ear complaints ( P < 0.012), and according to Damayanti et al ( 2022 ), human characteristics showed weak to moderate relationship with subjected hearing complaints. In other words, a strong relationship was recorded between exposure to noise intensity and subjected hearing complaints.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…The current study recorded high significant relation between audiometric notches and ear complaints ( P < 0.012), and according to Damayanti et al ( 2022 ), human characteristics showed weak to moderate relationship with subjected hearing complaints. In other words, a strong relationship was recorded between exposure to noise intensity and subjected hearing complaints.…”
Section: Discussionsupporting
confidence: 67%
“…This noise could cause complaints leading to several hearing disorders. Many factors can affect hearing like age, work period, and using equipment for ear protection (Damayanti et al 2022 ). Also, hearing damage at different levels was observed in many individuals who were exposed to a similar noisy environment, suggesting the definite role of genetic predisposing (interaction of genetic and environmental factors) (Bahaloo et al 2020 ; Taha et al 2022 ).…”
Section: Introductionmentioning
confidence: 99%